Interaction Between Strategy and Organizational Performance: The Influence of Family Management - Oro, Ieda Margarete (2017)
This article aims to analyze how occurs the interaction between business strategy and organizational performance in family firms. The research is classified as descriptive, with a qualitative approach, operationalized by the case study procedure. Data were collected through semi-structured interviews, documents and notices. Interviews were conducted with key informants and core family run. Evidence collected in the company searched, show that the business strategy with entrepreneurial attitude is characterized by the differentiation strategy (brand management) and product innovation (creation and development of new products) driven by family values disseminated within the organization. The results indicate that entrepreneurial orientation and family influence plays an important role for the realization of structural and strategic fit and, in turn, to the achievement of organizational performance.